Związek między profilem składników bioaktywnych a potencjałem antyoksydacyjnym ziarna w zależności od gatunku pszenicy i warunków uprawy = The relationship between profile of bioactive compounds and antioxidant potential of grain depending on the species of wheat and growing conditions - Skrajda, Marta Natalia; Konopka, Iwona Zofia (Journal of Education, Health and Sport, 2016)
Skrajda Marta Natalia, Konopka Iwona Zofia. Związek między profilem składników bioaktywnych a potencjałem antyoksydacyjnym ziarna w zależności od gatunku pszenicy i warunków uprawy = The relationship between profile of bioactive compounds and antioxidant potential of grain depending on the species of wheat and growing conditions. Journal of Education, Health and Sport. 2016;6(7):309-318. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57878 http://ojs.ukw.edu.pl/index.php/johs/article/view/3691 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. ZWIĄZEK MIĘDZY PROFILEM SKŁADNIKÓW BIOAKTYWNYCH A POTENCJAŁEM ANTYOKSYDACYJNYM ZIARNA W ZALEŻNOŚCI OD GATUNKU PSZENICY I WARUNKÓW UPRAWY The relationship between profile of bioactive compounds and antioxidant potential of grain depending on the species of wheat and growing conditions Marta Natalia Skrajda, Iwona Zofia Konopka Katedra Przetwórstwa i Chemii Surowców Roślinnych Wydział Nauki o Żywności, Uniwersytet Warmińsko-Mazurski w Olsztynie Uniwersytet Warmińsko-Mazurski w Olsztynie Katedra Przetwórstwa i Chemii Surowców Roślinnych Pl. Cieszyński 1, 10-726 Olsztyn e-mail: marta.skrajda@uwm.edu.pl Streszczenie Wprowadzenie i cel pracy: Ziarno pszenicy, będące głównym surowcem zbożowym na świecie, zawiera szereg małocząsteczkowych związków o właściwościach prozdrowotnych. Celem pracy było scharakteryzowanie głównych związków bioaktywnych pszenicy oraz czynników wpływających na ich akumulację. Skrócony opis stanu wiedzy: Małocząsteczkowe związki bioaktywne stanowią nawet do 2% masy ziarniaka pszenicy. Zalicza się do nich związki fenolowe (głównie kwas ferulowy), sterole (głównie β-sitosterol), tokole (głównie α-tokoferol i β-tokotrienol), karotenoidy (głównie luteina) oraz lipidy fenolowe znane jako alkilorezorcynole. Związki te tworzą potencjał antyoksydacyjny pszenicy, który według danych literaturowych mieści się w zakresie od 1 µmol TE g-1 do 140 µmol TE g-1. Różnice te zależą od odmiany, warunków środowiskowych, miejsca uprawy oraz interakcji między czynnikami środowiskowymi oraz genotypem. Podsumowanie: Na całym świecie podejmowane są próby określenia czynników determinujących koncentrację związków biologicznie aktywnych w ziarnie pszenicy. Uzyskiwane wyniki wciąż są jednak niejednoznaczne. Wskazuje się, że każdy składnik może reagować inaczej na warunki środowiskowe, przez co istnieje możliwość optymalizacji zawartości tych składników poprzez odpowiednią modyfikację warunków uprawy. Słowa kluczowe: pszenica, aktywność antyoksydacyjna, związki bioaktywne, genotyp. Abstract Introduction and aim: Food of plant origin contains a number of compounds with health-promoting properties. Wheat grain, which is the principal raw material grain throughout the world, is a good source of antioxidants. The aim of the study was to characterize the main bioactive compounds wheat and factors affecting their accumulation. Brief description of the state of knowledge: Antioxidants in wheat grains account for as much as 2% of the kernel weight. Both hydrophilic and hydrophobic forms are included in this group. They include phenolic compounds (mainly ferulic acid), sterols (mainly β-sitosterol), tocols (mainly α-tocopherol and β-tocotrienol), carotenoids (mainly lutein) and phenolic lipids known as alkylresorcinols. These compounds provide the antioxidant potential of wheat, which, according to the literature data, falls within the range from 1 µmol TE g-1 to 140 µmol TE g-1. These differences depend on the variety, environmental conditions, place of cultivation and the interactions between environmental factors and the genotype. Summary: All over the world, attempts are being made to identify factors determining the concentration of biologically active compounds in wheat. However, the obtained results are still inconclusive. Researchers have found that each component may react differently to environmental conditions, which allows them to see the possibility for the optimisation of the content of these components through the proper modification of environmental conditions. Key words: wheat, antioxidant activity, phytochemicals, genotype.